Strategies for the utilization of Atriplex plantations in a cereal-sheep pastoral zone of NW Murcia (Spain) - Correal E.; Sotomayor J.A. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
The balance of fodder resources versus feed requirements of 19 sheep-cereal farms in N.W.Murcia was analysed. The average farm -282 sheep and 319 ha- presents a feeding gap period in winter (3-4 months) during which sheep are supplemented with barley, straw and by-products from the canning industries, at an average cost of 15-20 US dollars per ewe. Atriplex plantations already exist in the zone promoted by the Administration to control soil erosion and create fodder banks for scarcity periods. From mean data on saltbush fodder production (3 ton DM per ha per year) and browse intake by sheep (1,5kgDM per ewe per day), it was estimated for the average farm that planting saltbushes on 4-6 per cent of its surface would cover the maintenance requirement of the sheep herd during the winter period.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)